Green Deal Challenges for a Sustainable Future of the EU - CIOT, Melania Gabriela (2024)
The European Green Deal (EGD), launched with the goal of makingEurope the world’s first climate-neutral continent by 2050, has redefinedthe contours of sustainable development, necessitating bold decisions,innovative policy frameworks, and the commitment of all stakeholders—governments, businesses, and citizens alike. An objective that putspressure on political leaders from the Member States to find suitablesolution for each European policy included in EGD to be implementedat national level. A lot of debates, conferences, groups were initiated,representatives of political decidents (policymaking), civil society,academia, market structures were called in this complex endeavor.Some Member States are on the right paths, trying to find goodsolutions for implementation and adjustment the EGD, some are stilldebating on the suitable policies to implement it, other have groups thatare contesting it or almost eludate the topic from the public agenda.